Productivity of Finger Millet (Eleusine coracana L.) as Influenced by Intra-row Spacing and Application of NPK Fertilizer Rates in Sudan Savanna, Nigeria (Sahel Journal of Life Sciences FUDMA, 2025)
Two field experiments were conducted concurrently during the 2024 rainy season at Gerki and Salahawa villages of Batagarawa Local Government Area, Katsina State, Nigeria, to determine the influence of three intra-row spacings and three NPK fertilizer application rates on the growth and yield of the finger millet variety. The trial was carried out with three intra row spacing (75 x 15cm, 75 x 20cm and 75 x 25cm) and three different rates of NPK fertilizer application (N30 P15 K15, N60 P30 K30 and N90 P45 K45) the treatments were factorize and laid under randomize complete block deign (RCBD) with three replications. Data on growth and yield-related components were recorded during the experiment. From the result obtained it is confirmed that intra-row spacing of 75 x 25cm significantly (P